A prospective, randomized, double blind study to evaluate and compare the efficacy of lidocaine, ramosetron and tramadol pre-medication, in attenuating the pain caused due to propofol injection - Zahoor, Ifra; Mir, Aabid Hussain; Qazi, Mohmad Syed; Jan, Zahoor Ahmad; Yousuf, Abida; Rasool, Ajaiz (International Journal of Research in Medical Sciences, 2017)
Background: Propofol is a popular induction agent, especially for short cases, day care surgeries and when a laryngeal mask is to be used. It produces a good quality of anaesthesia and rapid recovery. Pain on injection of propofol has been reported and is an important limitation of its use. A multitude of interventions: pharmacological as well as non-pharmacological, have been tried for the attenuation of pain caused due to propofol injection. In our study, we evaluated and compared the efficacy of lidocaine, ramosetron and tramadol in attenuating pain on propofol injection. Methods: A total of 180 patients belonging to American Society of Anesthesiologists (ASA) grade I and II, of either sex, aged between 21 to 50 years undergoing elective surgery under general anaesthesia, were taken up for the study and were divided into group A, B and C. Group A received 2ml of 2% (40mg) lidocaine, Group B received 2ml of ramosetron (0.3mg) and Group C received 1mg/kg of tramadol in 0.9% normal saline to make a total solution of 2ml. Venous occlusion was done by compressing forearm with tourniquet to increase the local concentration of drug after establishing an intravenous access. The study drug was injected over 10 seconds and then occlusion was removed after 60 seconds, followed by giving 25% of the total calculated dose (2.5mg/kg) of propofol (1% w/v in lipid base) injected over 20 seconds. This was followed by asking the patient about the severity of pain felt. The intensity of pain was graded using verbal rating scale (McCrirrick and Hunter) and was assessed at 0, 5, 10, 15 and 20 seconds, as after 20 seconds, the patient would be under the influence of propofol. Results: Lidocaine showed the best efficacy in attenuating propofol injection pain amongst the 3 groups recorded at 5 (95%), 10 (91.7%) and 15 seconds (98.3%). In addition to reducing the incidence of pain, it also reduced its severity, with majority of patients experiencing only mild pain. Ramosetron ranked 2nd in the overall reduction of propofol pain, with lowest incidence of propofol pain amongst 3 groups, recorded at 0 (98.3%) and 20 seconds (95%) of propofol injection. However, ramosetron failed in reducing severity of pain, with a significant number of patients experiencing moderate and severe pain. Tramadol ranked 3rd in the overall attenuation of propofol pain and showed lowest incidence of pain at 0 seconds (93%) of propofol injection. Conclusions: All the three study drugs viz lidocaine, ramosetron and tramadol cause a significant decrease in propofol injection pain with lidocaine as the most efficacious drug amongst the 3 drugs followed by ramosetron and tramadol. Lidocaine has an added advantage of decreasing incidence and severity of pain associated with propofol and ramosetron prevents postoperative nausea and vomiting.